2019
DOI: 10.3390/mi11010052
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Analysis of Neutrophils NETs by Microscopic LSPR Imaging System

Abstract: A simple microengraving cell monitoring method for neutrophil extracellular traps (NETs) released from single neutrophils has been realized using a polydimethylsiloxane (PDMS) microwell array (MWA) sheet on a plasmon chip platform. An imbalance between NETs formation and the succeeding degradation (NETosis) are considered associated with autoimmune disease and its pathogenesis. Thus, an alternative platform that can conduct monitoring of this activity on single cell level at minimum cost but with great sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The earlier processes collectively refer to NETosis, which is called lytic NETs [ 30 ]. NETosis generally takes around 3–4 h to complete [ 31 ]. Additionally, it has been discovered that the rapid formation and release of NETs can occur within 5–60 min without the need for neutrophil death [ 32 ].…”
Section: Mechanism Of Nets Formationmentioning
confidence: 99%
“…The earlier processes collectively refer to NETosis, which is called lytic NETs [ 30 ]. NETosis generally takes around 3–4 h to complete [ 31 ]. Additionally, it has been discovered that the rapid formation and release of NETs can occur within 5–60 min without the need for neutrophil death [ 32 ].…”
Section: Mechanism Of Nets Formationmentioning
confidence: 99%
“…This process only takes 5-60 minutes, which is different from the release of suicidal NOXdependent NETosis or NOX-independent NETosis lasting more than 3 hours. 125 At the end of this process, neutrophils eventually rupture and die. Yipp et al 45,126 proposed that the formation of nuclear DNA in rapid NETosis was dependent on the binding of LPS.…”
Section: Othersmentioning
confidence: 99%
“…These methods could prove to be a label-free alternative to current methods applied and developed for NET quantification [172]. In their microwell-based localized surface plasmon resonance based setup Ali et al demonstrated the label-free analysis of single neutrophil granulocytes following PMA treatment [173]. Deep-learning based image analysis based on bright-field microscopic images Hhaung et al were able to classify activated and inactivated neutrophils, with further improvement these efforts could prove to be useful later in image based WBC classification as well [174].…”
Section: Neutrophil Granulocytesmentioning
confidence: 99%